PERTUMBUHAN DAN HASIL TANAMAN SAWI (Brassica juncea L.) YANG TUMBUH PADA BERBAGAI MEDIA TANAM DAN PEMBERIAN PUPUK ORGANIK CAIR - Sitti Patima; Sakka Samudin; Ramal Yusuf (Agroland: Jurnal Ilmu-ilmu Pertanian, 2014)
The experiment aimed to study the effect of media and to see the effect ofliquid organic fertilizer taking from goat manure on growth yield of mustard. This research has been conducted in the green house Faculty of Agriculture, University of Tadulako Palu from March 2014-April 2014. The research using Randomized Block Design (RBD), two factors. The first factor is the use of various types of media that is soil (M1); soil+sawdust (M2); soil+rice husk (M3). The second factor a liquid organic fertilizer of goat manure consisting of 3 levels ie1.6% liquid organic fertilizer/plant (C1), giving 2.4% /plants (C2) and the provision of 3.2% /plants (C3). Thus there are 9 treatment combination srepeated 3 times, so there are 27 experimental units. The results showed the use of various types of media and liquid organic fertilizer in fluence on components of plant height, leaf number, leaf area, fresh weight of root, leaf fresh weight, root dry weight, and dry weight of the plant leaf.  Based on the results of the study showed that aplication of 3.2% liquid organic fertilizer/plant (C3) in the mustard plant significant effectonall components of the observation. Medium soil+rice husk (M3) effect on growth of mustard. The interaction between the concentration of liquid organic fertilizers and media significant effecton the components of plant height, leaf area, fresh weight of roots, leaf fresh weight, root dry weight, dry weight of the leaf. Key Words : Mustard Plants, media, liquid organic fertilizer.